2021
DOI: 10.1002/admi.202001873
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol–Silicone Membranes for Sustained and Controlled Topical Delivery of Antimicrobial and Pain‐Relief Drugs

Abstract: Controlling drug delivery from medical dressings to wounds remains a challenge despite the presence of multiple drug‐containing wound dressings on the market. The dressing should ideally be effective immediately after application and still show no burst effect, and must also be comfortable for an extended period of time. Here, a silicone‐based membrane is shown to offer an adjustable, constant release of various drugs even at a minimum moisture level resembling that of dry wounds. The drugs are dissolved in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The antimicrobial susceptibility assay was carried out as previously described. 50 Eight bacterial species (represented by a total of 10 strains) that are commonly found on the human skin and/or in acute and chronic wounds were investigated. The GSE membranes were placed onto the agar, and the plates incubated at 35 C for 18-20 h. Subsequently, the diameters of the growth-inhibition zones were measured.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The antimicrobial susceptibility assay was carried out as previously described. 50 Eight bacterial species (represented by a total of 10 strains) that are commonly found on the human skin and/or in acute and chronic wounds were investigated. The GSE membranes were placed onto the agar, and the plates incubated at 35 C for 18-20 h. Subsequently, the diameters of the growth-inhibition zones were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The results of an antimicrobial study published recently confirmed that the GSE membranes containing TCS are effective against a variety of bacterial strains. 50 Importantly, the membranes performed substantially better when compared to two state-of-the-art commercially available antimicrobial wound dressings. Here, we investigate the antimicrobial action of the GSE membranes loaded with TET and MUP.…”
Section: Antimicrobial Activity Of Singlecompartment Gse Membranesmentioning
confidence: 96%
See 3 more Smart Citations